The desire to leave a positive legacy will make a better transformational leader - Chandra, Adi; Meilani, Yohana (Institute of Computer Science (IOCS), 2023)
This research shows transformational leaders with a desire to leave a positive legacy will make the leader become better transformational leaders. Previous research only shows the positive impact of transformational leadership while the leaders are still around in the company which are short-term impact. It is therefore argued, that if the transformational leader extends his/her view and will to a longer time horizon and has a desire to leave a positive legacy, he/she will prepare/build a stronger impact on the company and the impact and contribution will last forever even if they are no longer in a position. This research uses a fast review method of the current literature to develop the argument. This research will give a fresh perspective on transformational leadership and legacy leadership